Efficiency of Islamic Insurance in Indonesia - Rachma Indrarini; Clarashinta Canggih (IQTISHODUNA: Jurnal Ekonomi Islam, 2019)
This paper aims to measure Islamic Insurance Efficiency in Indonesia. This paper uses quantitative data analysis through Data Envelopment Analysis to assess efficiency. Input variables in this study are total assets, expenses, and claims payments, while the output variables used are tabaru income and funds during 2012-2016. The objects of this paper are PT. AJS Amanahjiwa Giri Arta, PT AJS Al Amin, and PT Asuransi Takaful Keluarga. The result shows that in general, Islamic insurance in Indonesia is not yet efficient.